Application of Bokashi Swallow Dirt to Some Properties of Land Chemistry and Growth and Results of Plant of Red Branch (Capsicum annum L.) - Rini Alvionita (Mulawarman University, 2018)
The purpose of this study was to determine the best dose of swallow droppings that affect soil chemical properties with parameters of pH, Organic C, N, P, K on the soil and growth and yield of red chili. This research was carried out for 6 months starting from July 2017 to January 2018. The research location was on Jl. Mount Lingai North Samarinda. The design used was Randomized Block Design (RBD) consisting of five treatments and five replications. (P0) 0 g bokashi swallow bird polybag-1, (P1) 50 g bokashi swallow bird polybag-1, (P2) 100 g polybag-1, (P3) 150 g polybag-1, (P4) 200 g polybag-1. Soil seals were composted, then analyzed with soil pH parameters, organic C, N, P, K. The soil data obtained were analyzed based on the status of soil chemical research that had been developed by the Bogor research center in 2005. Plant data analyzed were plant height, number fruit/plant and fruit/plant weight. Plant data obtained were analyzed using variance, and followed by LSD testing at the level of 5%. The results of this study indicate that giving bokashi swallow droppings with a dose of 200 polybag-1 in P4 treatment showed an influence on some soil chemical properties, including soil pH from 5.01 to 5.31 with acid status; Organic C from 1.92 to 4.79 with very high status; Phosphorus (P) from 17.05 to 176.82 with very high status; Potassium (K) from 23.89 to 78.22 with a very high status on the soil. Meanwhile, Nitrogen (N) has decreased N levels from 0.26 to 0.25 with very low status on the soil. The bokashi application of swallow droppings showed a very different effect on the high growth of red chilli plants, while the yield of plants was not significantly different, namely the number of fruit and the weight of fruit/red pepper plants. The best response was found in P4 treatment which used a dose of 200 g polybag-1 with an average plant height of 32.12 cm; average number of fruits/plants 3.00; average fruit/plant weight 22.32 g.